Effects of head-only or whole-body exposure to very low doses of 4He (1000 MeV/n) particles on neuronal function and cognitive performance. (February 2019) - Rabin, Bernard M.; Poulose, Shibu M.; Bielinski, Donna F.; Shukitt-Hale, Barbara
Abstract: On exploratory class missions, astronauts will be exposed to a range of heavy particles which vary in linear energy transfer (LET). Previous research has shown a direct relationship between particle LET and cognitive performance such that, as particle LET decreases the dose needed to affect cognitive performance also decreases. Because a significant portion of the total dose experienced by astronauts may be expected to come from exposure to low LET 4 He particles, it would be important to establish the threshold dose of 4 He particles that can produce changes in cognitive performance. The results indicated that changes in neuronal function and cognitive performance could be observed following both head-only and whole-body exposures to 4 He particles at doses as low as 0.01–0.025 cGy. These results, therefore, suggest the possibility that astronauts on exploratory class missions may be at a greater risk for HZE-induced deficits than previously anticipated.